Magnetic Nanoparticle‐Based Upregulation of B‐Cell Lymphoma 2 Enhances Bone Regeneration. (January 2017) - Brett, Elizabeth; Zielins, Elizabeth R.; Luan, Anna; Ooi, Chin Chun; Shailendra, Siny; Atashroo, David; Menon, Siddarth; Blackshear, Charles; Flacco, John; Quarto, Natalina; Wang, Shan X.; Longaker, Michael T.; et al.
Abstract: Clinical translation of cell‐based strategies for tissue regeneration remains challenging because survival of implanted cells within hostile, hypoxic wound environments is uncertain. Overexpression of B‐cell lymphoma 2 (Bcl‐2) has been shown to inhibit apoptosis in implanted cells. The present study describes an "off the shelf" prefabricated scaffold integrated with magnetic nanoparticles (MNPs) used to upregulate Bcl‐2 expression in implanted adipose‐derived stromal cells for bone regeneration. Iron oxide cores were sequentially coated with branched polyethyleneimine, minicircle plasmid encoding green fluorescent protein and Bcl‐2, and poly‐β‐amino ester. Through in vitro assays, increased osteogenic potential and biological resilience were demonstrated in the magnetofected group over control and nucleofected groups. Similarly, our in vivo calvarial defect study showed that magnetofection had an efficiency rate of 30%, which in turn resulted in significantly more healing compared with control group and nucleofected group. Our novel, prefabricated MNP‐integrated scaffold allows for in situ postimplant temporospatial control of cell transfection to augment bone regeneration. Stem Cells Translational Medicine 2017;6:151–160